Improvement in accuracy of natural frequency determination based on the envelope of cross-correlation function - Kotowski, Adam (Advances in Mechanical and Materials Engineering)
This paper presents a method of improvement of the accuracy in natural frequency determination when having impulse responses from impact testing. A new method is used for obtaining impulse response spectrum. The improvement in natural frequency determination is a result of improving the spectral resolution. For this, the new method uses calculation of surface area under the envelope of the cross-correlation function. This process is repeated by single-harmonic signal generated step-by-step with frequency changed iteratively. Thus the frequency resolution of determined spectrum is independent of length of analysed impulse response.